Determining the allowable opening-to-traffic asphalt temperature for airport pavements - Rahman, Taqia; Dawson, Andrew; Thom, Nick; Ahmed, Imtiaz; Carvajal-Munoz, Juan S. (Taylor & Francis, 2020)
Newly laid asphalt must be adequately cool before it can be trafficked to prevent the development of costly premature damage. Selecting an appropriate traffic-opening temperature of newly laid asphalt airport runway overlay would avoid early damage – while also minimising the disruption to the airport service due to prolonged runway closure in a busy airport. This study aims to investigate the allowable traffic-opening temperature of freshly paved asphalt during nighttime construction through a series of laboratory tests with regard to asphalt rutting and interface shear failure potential. Additionally, a transient heat transfer model is developed to study the cooling response of freshly laid asphalt and, along with stress analysis, used to deduce the effect of selected critical traffic opening to traffic on airport closure. The results suggest that mixtures with polymer-modified bitumen (PMB) can be re-opened to air traffic at a considerably higher temperature (up to 80°C) than conventional trafficopening temperature as set by many agencies (60°C). This result encourages airport authorities and agencies to be more adaptive with the traffic-opening temperature specification, particularly for asphalt with PMBs. For the cases studied, raising the critical trafficking temperature would reduce the runway/airport closure during nighttime construction by 17–114 minutes (26–63% reductions).